The cerrado as a Brazilian national heritage: Subsidies for the conservation of its flora - Peixoto, Josana de Castro; Ribeiro, Charles Lima; Castro, Joana D’arc Bardella; Carvalho, Glennya Rodrigues (Seven Editora, 2023)
This chapter aims to reflect on the urgency of approving the Proposed Constitutional Amendment No. 504 of 2010, which amends § 4 of Article 225 of the Federal Constitution of 1988 to include the Cerrado and Caatinga among the biomes considered as national heritage.   This study discusses the importance of preserving the aforementioned biomes and their treatment as national heritage, in order to preserve not only their biodiversity, but also to discuss the rational use of agriculture and agribusiness. Thus, after presenting brief excerpts about the phytosionomy of the Cerrado and Caatinga, and the necessary reasons for the approval of the Proposed Constitutional Amendment, it is that the article addresses the constitutional hermeneutics to justify the change of article 225 and why the subject under debate is treated at the constitutional level and not infraconstitutional. Therefore, it is understood that, with this measure, to provide the ideal constitutional legal protection of these biomes, the Brazilian population, especially the people who live in the Midwest and Northeast Regions of Brazil, will value the Cerrado and the Caatinga, as vital elements of their existence, their culture, their heritage, taking better care of them, so that, the aforementioned article 225, have your goal set in its fullness. It is these debates and reflections that we intend to bring to this scientific article. For this, the qualitative method was used through the bibliographic research modality, using literature that discusses the theme.DOI:https://doi.org/10.56238/alookdevelopv1-113